BET 1: Prednisolone for the treatment of acute gouty arthritis. Issue 10 (28th September 2017) - Simon Taylor, Richard
Abstract : A short cut review was carried out to establish whether corticosteroids are safe and effective in managing the symptoms of acute gouty arthritis. Five studies were directly relevant to the question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. The clinical bottom line is that corticosteroids are an effective and safe alternative to non steroidal anti inflammatory drugs (NSAIDs) in patients presenting with acute gouty arthritis.